Growth and mineral composition of the melon with different doses of phosphorus and organic matter - da Silva Gomes, Jonath Werissimo [UNESP]; da Silva Dias, Nildo; Moreno-Pizani, Maria Alejandra; de Paiva, Kariolania Fortunato; Rocha, Josinaldo Lopes Araujo; Araújo, Erbia Bressia Gonçalves; dos Santos Fernandes, Cleyton (Universidad Nacional de Colombia, 2019)
It was aimed to evaluate the effect of doses of phosphorus and different doses of bovine manure on growth of melon Galia. The experiment was carried out in greenhouse utilizing pots filled with soil Chromic Luvissoil in design completely randomized with a 5 x 2 factorial arrangement, comprising five doses of bovine manure (0, 12, 16, 20, 24 t ha-1) and two doses of phosphorus (0 and 400 mg dm-3), with three replicates, totaling 30 experimental units. The results indicated that interaction of phosphorus with organic matter was significant effect on total dry mass of the melon plant. There was a reduction of the total dry mass when the plants were fertilized at the highest doses of bovine manure. The P content from leaf and stem increased gradually at higher doses of phosphorus. The phosphorus content in the soil increased according to the doses of organic material available.
Crecimiento y composición mineral del melón con diferentes dosis de fósforo y materia orgánica
Keywords: Cucumis melo L.; Organic fertilization; Phosphate fertilization